Diagenetic and hydrothermal events revealed by an Ediacaran dolomite breccia from the Araras-Alto Paraguai basin, southern Amazon Craton - Sepeda, L. F. (2024)
The establishment of extensive carbonate platforms characterized the Ediacaran period during CaCO3 oversaturation events and the exceptional creation of accommodation space associated with the aftermath of the Marinoan glaciation (∼635 Ma). Carbonate deposits in the Araras Group record the early Ediacaran period, stage 1, in the Amazon Craton. The Serra do Quilombo Formation is an intermediate unit characterized by heavily fractured and faulted dolomites, as well as the presence of dolomite-cemented breccias (CB) overlying thick limestone packages associated with diagenetic and hydrothermal modifications. These features are commonly attributed to structurally controlled hydrothermal dolomitization (HTD) and are of significant economic importance as hydrocarbon reservoirs and Mississippi Valley-type (MVT) lead-zinc mineralization hosts. This study aims to unravel the origin of cemented breccias and the diagenetic/burial processes within the unit, focusing on dolomitization processes. Dolomite samples were analyzed using petrographic, scanning electron microscopy, microprobe, micro-Raman, cathodoluminescence, and isotopic analyses (δ13C, δ18O, 87Sr/86Sr) to unravel their burial history. CBs are sub-vertical to sub-horizontal bodies with complex geometries, generally cutting bedding at high angles, indicating hydrofracturing processes related to vertical flows of hydrothermal fluids (hydraulic breccia) and present the typical cockade texture of expansion breccias in dilatational faults. The substitutive matrix RD1 is the main constituent of the Serra Quilombo Formation, its low correlation between δ13C and δ18O (R2 = 0.009), the well-preserved fabric, and the similarity with the isotopic values (C and Sr) documented for Ediacaran carbonates, suggest that the syndepositional dolomitization. The first generation of dolomite cement (DC1) and the last phase of dolomitic cementation (saddle dolomite - SD) occur, filling pores, CBs, and fractures. The cockade texture of the breccias evidences a low precipitation rate or a pause in precipitation between DC1 and SD. Concurrently, DC1 has isotopic signals of δ18O = −4.34 ± 1.32‰ (n = 18) and 87Sr/86Sr = 0.708831 (n = 2), while SD has values of δ18O = −9.57 ± 2.51‰ (n = 15) and 87Sr/86Sr = 0.711464 (n = 3). The large isotopic fractionation between DC1 and SD suggests different dolomitizing fluids. This relationship shows an increase in 87Sr in the fluid as the temperature increases; moreover, the enrichment in 87Sr of the fluid is explained by the interaction of this fluid with rocks from the crystalline basement. Thus, the main conduit for the ascent of this radiogenic fluid would be faults with deep roots spatially close to tectonically active zones. Lastly, the presence of tectonic stylolites cutting cemented breccias and rotated zebra-like strata-bound structures suggests that brecciation occurred before the installation of fragile post-Ordovician transtensional structures, preceding the establishment of Paleozoic Basins on the South American Platform.